Limitation of Opinion With Social Media Take Down System, is Indonesia Toward to Totalitrism? - Harrel Ciddan; Ailsa Fitri Shafwa; Abim Prima Prayoga; Navita Fayola Frihanggrahita; Fakhris Aulady; Ali Imron (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Indonesia is a country with a democratic government system so that Indonesia provides equal treatment, rights and obligations to all its people. Freedom of opinion is a right owned by every human being that is guaranteed by a state, as contained in Article 28E paragraph (3) which reads